(untitled) - Santurette, Patrick (London, 2005)
A practical guide to using potential vorticity fields and water vapor imagery from satellites to elucidate complex weather patterns and train meteorologists to improve operational forecasting.
Keywords: Satellite meteorology,Water vapor, atmospheric,Weather forecasting